1988
DOI: 10.1111/j.1399-6576.1988.tb02806.x
|View full text |Cite
|
Sign up to set email alerts
|

Local anaesthesia efficacy: discrepancies between in vitro and in vivo studies

Abstract: Electrophysiological studies on isolated nerves have been used extensively in the past to assess the comparative efficiency of local anaesthetics as agents of peripheral nerve blockade. It is shown here that three closely related amide local anaesthetics behave differently in vitro and in vivo. In terms of onset of action and of maximum suppression of the evoked action potential, mepivacaine proved a less efficient anaesthetic than lidocaine or prilocaine on isolated nerves, but in parallel studies on the scia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
4

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
3
0
4
Order By: Relevance
“…Given that the nerve membranes are made of lipoproteins, this allows the anaesthetics to have faster membrane penetration for a quicker onset. The pKa values of mepivacaine and lidocaine are 7.6 and 7.9 respectively . The closer to physiologic pH (7.4) a drug is, the quicker the onset of action.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the nerve membranes are made of lipoproteins, this allows the anaesthetics to have faster membrane penetration for a quicker onset. The pKa values of mepivacaine and lidocaine are 7.6 and 7.9 respectively . The closer to physiologic pH (7.4) a drug is, the quicker the onset of action.…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies, 3% mepivacaine depressed the compound action potential (CAP) of the rat sciatic nerve better than did 2% lidocaine (Pateromichelakis and Prokopiou, 1988). Articaine (4%) was more effective than 2% lidocaine in blocking conduction in the frog (Muschaweck and Rippel, 1974) or rat peripheral nerve (Stankovic v ova and Štolc, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Comparing isomers to racemic bupivacaine, an in vitro study 13 has shown that the dextrogyrous one is more potent (1.36), the levogyrous is less potent (0.45) and the 50% enantiomeric excess bupivacaine has similar potency (0.88). However, the clinical use of local anesthetics is more complex than what has been shown in animals, and in vivo potencies do not correlate to in vitro results 14 . Local factors affecting anesthetic spread and block extension are of major impact on clinical effects.…”
Section: Discussionmentioning
confidence: 99%
“…As falhas foram parciais, havendo complementação com dose adicional e sedação em todas as pacientes.DISCUSSÃONeste estudo foi observada a homogeneidade demográfica entre os grupos com exceção da idade sendo esta maior no grupo I. Embora este dado seja provavelmente casual em razão do tamanho da amostra, a idade, como fator isolado, apresenta pouca influência no bloqueio peridural em adultos, mas ganha importância, quando se considera a população de crianças e idosos 5 . Avaliação do Bloqueio Sensitivo acima de T 4 mais complexo do que o demonstrado em animais, sendo que as potências in vivo não se correlacionam às encontradas in vitro14 . Os fatores locais que afetam a difusão e a extensão do anestésico local representam fator de grande impacto sobre os efeitos clínicos.…”
unclassified